Pengembangan Media Pembelajaran Berbasis Kartu Visual Sikuen untuk Anak Autis - Tiffani Dwi Safira Rosa; Mierrina Mierrina (STKIP Subang, 2025)
This study is based on the results of a needs analysis of autistic children who face difficulties in understanding verbal instructions during the learning process and therapy as well as the inability to carry out daily activities independently which makes them still require assistance. The dominant learning method is oral and not in accordance with the learning style of autistic children, so it requires concrete visual media support. The purpose of this research is to develop visual sequencing cards as an alternative learning media for autistic children. This research uses the R&D method (Research and Development) that adapts the ADDIE model. Data was collected through observation, interviews, and documentation. The data analysis technique is carried out through several stages, namely data reduction, data presentation, and drawing conclusions from data obtained from the results of interviews, observations, and documentation. The result of this study is the development of visual sequencing cards as a practical and innovative learning medium for autistic children. This research contributes to the provision of visual-based learning media that applies theory as a conceptual basis so that it can support learning to increase the independence and understanding of children with autism.